Caregiving stressors and sleep outcomes: examining group differences among caregivers of persons living with dementia. - Wang, Fei; Cho, Seungjong; Conway, Anne; Heo, Yejin; Lau, Christine; Machry, Karyne (Journals of Gerontology Series B: Psychological Sciences & Social Sciences, 2026)
Objectives Caring for persons living with dementia often involves high levels of physical demands and emotional burden, which may undermine caregivers' sleep quality. Few studies have examined sleep health among Black caregivers of persons living with dementia, despite the fact that they are underrepresented in dementia research and experience poorer sleep outcomes compared to non-Hispanic White caregivers. This study aimed to examine the relationships between caregiving stressors and sleep health among family caregivers of persons living with dementia and whether these relationships differ between Black and non-Hispanic White caregivers. Methods Data were drawn from 288 Black (M = 59.91) and non-Hispanic White (M = 62.67) caregivers of persons living with dementia (>64 years old) in the 2017 National Study of Caregiving. Sleep outcomes included sleep disturbance and prior-night sleep difficulty. Hierarchical multiple linear regression models were conducted to examine the study aims. Results Subjective caregiving stressor (i.e. role overload) was positively associated with sleep disturbance. A significant interaction showed that the association between role overload and sleep disturbance was stronger among Black caregivers than in non-Hispanic White caregivers. Discussion The study identifies the detrimental role of role overload for caregiver sleep health. Findings also suggest that Black caregivers of persons living with dementia may experience greater vulnerability to the adverse role of role overload in relation to sleep. Further research is needed to better understand Black caregivers' experiences and the potential role of culturally appropriate interventions in improving their sleep health.